2021
DOI: 10.1108/ijssp-04-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Locating Central and Eastern European emerging welfare regimes: is the youth welfare citizenship typology useful?

Abstract: Purpose The authors’ aim is to establish the variance of youth welfare citizenship regimes in Central and Eastern Europe (CEE) and to revisit the applicability of the regime approach to the emerging welfare regimes (EWRs). Design/methodology/approach The empirical analysis follows the descriptive case study strategy aiming to discover diversity of youth welfare citizenship patterns. The case selection is made within the CEE country group, which includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…At the same time, Broka and Toots (2022) analysed youth welfare citizenship using selective/inclusive dichotomy. They found that all three Baltic countries represent the inclusive type.…”
Section: The Effectiveness Of Almp For Rural Neets In Lithuaniamentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, Broka and Toots (2022) analysed youth welfare citizenship using selective/inclusive dichotomy. They found that all three Baltic countries represent the inclusive type.…”
Section: The Effectiveness Of Almp For Rural Neets In Lithuaniamentioning
confidence: 99%
“…They found that all three Baltic countries represent the inclusive type. The inclusive type is characterised by a low level of school dropout, high shares of students in vocational training and education (VET); high school enrolment rate, low youth unemployment; low NEET rate; low work poverty; high participation at youth-oriented ALMP; high youth employment rate (Broka & Toots, 2022). As for the Baltic countries, Latvia can be clearly distinguished with its focus on training initiatives.…”
Section: The Effectiveness Of Almp For Rural Neets In Lithuaniamentioning
confidence: 99%
See 1 more Smart Citation
“…Broka and Toots (2021) fill a gap in welfare regime literature by revisiting the youth welfare citizenship regimes typology developed by Chevalier (2016) for consolidated welfare states in six Central and Eastern European (CEE) countries. Rather than simply placing all CEE countries into a simplistic “post-communist” regime, the authors conduct a cross-country examination adapting Chevalier's indicators to CEE reality.…”
Section: State Of the Art And Diversity Across Emerging Welfare Statesmentioning
confidence: 99%
“…cash transfers, care, youth, taxation, education, health and others). The studies examine responses and challenges of social policy systems in Mozambique, Uganda, Ghana, Zambia and South Africa (Gasior et al , 2021), Brazil and Mexico (Tomazini, 2021), Estonia, Latvia, Lithuania, Croatia, Slovenia and Bulgaria (Broka and Toots, 2021), Ecuador (Ubasart-González and Minteguiaga, 2021), India (Nakray, 2021), Japan (Milly, 2021), Austria (Landini, 2021), Mexico (Martínez-Martínez et al , 2021), Greece (Burgi and Kyramargiou, 2021) and 15 post-Soviet states [1] (Panaro, 2021). Most papers refer to emerging welfare states, and some discuss social policies in more consolidated social policy systems, such as the cases of Austria, Greece and Japan, which are currently facing challenges that involve citizens from emerging welfare states.…”
mentioning
confidence: 99%